2014
DOI: 10.1590/0004-2730000003080
|View full text |Cite
|
Sign up to set email alerts
|

Importância do viés de memória na obtenção da idade da menarca pelo método recordatório em adolescentes brasileiras

Abstract: RESUMOObjetivo: Comparar a idade da menarca obtida pelo método recordatório conforme o tempo decorrido desde o evento para verificar a importância do viés de memória. Sujeitos e métodos: Foram avaliadas 1.671 meninas (7-18 anos) em escolas de Campinas-SP quanto à ocorrência da menarca, pelos métodos status quo (menarca: sim ou não) e recordatório, (data da menarca, para as que a referiram). A idade da ocorrência do evento obtida pelo status quo foi calculada pelo logito, que considera todo o grupo, e a obtida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Finally, the age at menarche was self-reported. It is known that age at menarche based on recall data is not very accurate, especially when the time between menarche and current age is more than three years (37). However, other studies have shown high correlations (R=0.67 to 0.79) between age at menarche by recall during middle-age and the original childhood data (38).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the age at menarche was self-reported. It is known that age at menarche based on recall data is not very accurate, especially when the time between menarche and current age is more than three years (37). However, other studies have shown high correlations (R=0.67 to 0.79) between age at menarche by recall during middle-age and the original childhood data (38).…”
Section: Discussionmentioning
confidence: 99%
“…Women may remember the year but not the exact date of the menarche; however, previous studies demonstrated good reliability of the approximated age at menarche. 17 This should be taken into account since the previous studies reported significant differences based on a very small difference (months) of onset of menarche between the groups. 9 It is therefore difficult to establish a causal relationship between that small difference in age at menarche reported in previous studies and the risk of such a complex disease as MS. To overcome this limitation in the future, we have started to collect this information prospectively.…”
Section: Discussionmentioning
confidence: 96%
“…The risk of recall bias may be greater in urban young adult women as they are two years older than their rural counterparts. However, this method is commonly used to obtain the age at menarche and it has been shown that adult women are reliable when they report their age at menarche (Castilho et al., 2014 ). Secondly, we could not adjust our analysis for birthweight or childhood adiposity.…”
Section: Discussionmentioning
confidence: 99%